Short-term Indian Experience with Micropulse Transscleral Cyclophotocoagulation Using Revised Micropulse Probe in Advanced Glaucoma - M. Salu; Murali Ariga; K. Jeyasudha Roopesh; Pratheebadevi Nivean (Delhi Journal of Ophthalmology)
Introduction: Micropulse transscleral laser therapy, commonly referred to as micropulse transscleral cyclophotocoagulation (MP-TSCPC), is a safe and effective treatment for glaucoma. Objective: To evaluate the mean intraocular pressure (IOP)-lowering effect of micropulse diode laser cyclophotocoagulation performed using a revised micropulse probe and to observe any adverse events. Materials and Methods: A single-center retrospective study included 34 patients diagnosed with advanced glaucoma who underwent micropulse transscleral cyclophotocoagulation using a revised micropulse P3 probe. Data were collected from the electronic medical records of patients. Data noted at baseline-demographics, best-corrected visual acuity, IOP, prior glaucoma surgeries, and the number of anti-glaucoma medications. The procedure was performed by a single surgeon with standard laser settings. The eye was patched with topical moxifloxacin 0.5% combined with dexamethasone 0.1%. Anti-glaucoma medications were continued postoperatively. Postoperative data-IOP and the number of anti-glaucoma medications at postoperative 1 week and 3 months were noted. Results: Statistical analysis was performed using Minitab 19. Mean IOP (in mmHg) at baseline was 31.64 ± 6.97, and 22.20 ± 8.57 and 21.82 ± 7.56 at postoperative 1 week and 3 months, respectively, (P < 0.001). The mean number of antiglaucoma medications at baseline was 3.5 ± 0.74 and at 1 week after MP-TSCPC was 2.97 ± 0.79 and at 3rd month was 2.97 ± 0.83 (P < 0.001). Conclusion: MP-TSCPC using the revised micropulse probe is effective in lowering IOP, has an acceptable safety profile and tolerability, and can be considered for patients with advanced glaucoma.